2014
DOI: 10.1063/1.4893980
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of halide solid solutions: Measurement and prediction

Abstract: The composition dependence of the lattice thermal conductivity in NaCl-KCl solid solutions has been measured as a function of composition and temperature. Samples with systematically varied compositions were prepared and the laser flash technique was used to determine the thermal diffusivity from 373 K to 823 K. A theoretical model, based on the Debye approximation of phonon density of state (which contains no adjustable parameters) was used to predict the thermal conductivity of both stoichiometric compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…tion as functions of temperature and composition. The EMD prediction of the thermal conductivity of pure NaCl at 900 K is in very good agreement with the critically assessed value reported by Gheribi et al, 17 with a di↵erence of about 5%. Unlike the NaCl case, the accuracy of about 25% obtained for KCl is relatively poor.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…tion as functions of temperature and composition. The EMD prediction of the thermal conductivity of pure NaCl at 900 K is in very good agreement with the critically assessed value reported by Gheribi et al, 17 with a di↵erence of about 5%. Unlike the NaCl case, the accuracy of about 25% obtained for KCl is relatively poor.…”
Section: Resultssupporting
confidence: 88%
“…For all compositions, we have observed that (⌧) reaches a plateau before 10 ps and the thermal conductivity values were calculated by averaging (⌧) for ⌧ 10 ps. 17 The EMD simulations (filled stars symbols) have been performed only at 900 K. The critically assessed values 17 of the thermal conductivity of pure NaCl and KCl compounds at 900 K are also reported (filled square). Point interpolation were splined (dashed lines).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations